Comparison of the cytobrush, cytotape and uterine lavage techniques in healthy postpartum cows - RANA, ANCHAL; SINGH, MADHUMEET; KUMAR, PRAVESH; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2020)
This study was conducted to compare the accuracy of three different techniques of endometrial cytology to diagnose sub-clinical endometritis in dairy cows. Postpartum dairy cows (21) with history of normal calving were selected for obtaining endometrial samples at weekly interval from day 14 to 42 postpartum. In each cow, samples were obtained in a sequential manner, first with the cytotape, then with the cytobrush followed by uterine lavage. Smears were stained with Giemsa stain method. Parameters used to evaluate these techniques were; presence of polymorphoneutophils (%), total cellularity, red blood cell contamination and quality of the smears. No difference was recorded between the three techniques in % polymorphoneutrophils recovered. All techniques provided diagnostic samples; however, cytotape yielded the highest quality sample. On the other hand, cytobrush and cytotape methods yielded similar total cellularity (P=0.3781), uterine lavage yielded significantly (P